High-strength anti-fatigue continuous aramid fiber / unsaturated polyester resin composite material and preparation method thereof

By performing the surface modification of the polyethyleneimine-polydopamine and the layer-layer arrangement of the bionic structure of continuous aramid fibers, the problem of insufficient bonding between fibers and resins is solved, and the tensile strength and fatigue resistance of the composite material are significantly improved.

CN119735835AActive Publication Date: 2025-04-01TAIYUAN UNIVERSITY OF TECHNOLOGY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411634322.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-01
Estimated Expiration
2044-11-15

Smart Images

  • Figure CN119735835A_ABST
    Figure CN119735835A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer composite materials, and provides a high-strength anti-fatigue continuous aramid fiber / unsaturated polyester resin composite material and a preparation method thereof. The preparation method comprises the following steps: by taking unsaturated polyester resin as a matrix and polyethyleneimine-polydopamine modified continuous aramid fiber as a reinforcement body, grafting polydopamine and polyethyleneimine onto the continuous aramid fiber through Michael addition reaction and Schiff base reaction of the polydopamine and the polyethyleneimine; meanwhile, the modified continuous aramid fiber simulates a collagenous fiber arrangement structure of a compact bone, the high-strength anti-fatigue continuous aramid fiber / unsaturated polyester resin composite material is prepared, the interface bonding strength of the composite material reaches 40.60 MPa, the tensile strength reaches 959.07 MPa, and the fatigue life of the composite material under 600 MPa reaches 760,000 times; the fatigue life of the composite material reaches 10470000 times under the condition of 500 MPa, and the fatigue life of the composite material reaches 87100000 times under the condition of 400 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, relates to the modification of fibers in composite materials and the mechanical properties of composite materials, and more specifically to a high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material and a preparation method thereof. Background Art

[0002] High-performance continuous fiber reinforced polymer composites are composite materials formed by combining high-strength continuous fibers with a resin matrix. The resin matrix, as the binder of the continuous fiber reinforcement, is responsible for transferring the load between the fibers. The continuous fiber, as the reinforcement of the matrix, is the main supporter of the high strength of the continuous fiber composite. High-performance continuous fiber reinforced polymer composites are gradually replacing traditional structural materials such as metals with their superior mechanical properties, good environmental stability and lightweight. Continuous aramid fiber, as an organic fiber composite material, has attracted much attention in continuous fiber reinforced composites. However, although continuous aramid fiber has excellent performance, it has poor bonding with most resin matrices due to its high orientation and inert surface. In order to improve this shortcoming of aramid fiber, researchers have improved the interfacial bonding performance between aramid fiber and resin matrix by surface modification of aramid fiber.

[0003] At the same time, the arrangement structure of fibers in composite materials is crucial to the mechanical properties of composite materials. To date, many researchers have prepared fiber composite materials with excellent strength and toughness by imitating natural structures, which have broad application prospects in various fields. Summary of the invention

[0004] In order to improve the mechanical properties of a continuous aramid fiber / unsaturated polyester resin composite material, the present invention provides a high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material and a preparation method thereof.

[0005] The present invention simply modifies the continuous aramid fiber, strengthens the bonding strength between the aramid fiber and the unsaturated polyester resin matrix, and improves the tensile strength and fatigue resistance of the continuous aramid fiber / unsaturated polyester resin composite material.

[0006] The present invention is achieved by the following technical scheme: a method for preparing a high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material, which uses unsaturated polyester resin as a matrix and polyethyleneimine-polydopamine modified continuous aramid fiber as a reinforcement, and the modified continuous aramid fiber is biomimetic of the collagen fiber arrangement structure of compact bone to prepare a high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material.

[0007] Further, the following steps are included: (1) Surface modification of continuous aramid fibers: The continuous aramid fibers were pretreated by soaking in ethyl acetate for 24 hours to remove impurities on the fiber surface and then dried; A mixed solution of polydopamine and polyethyleneimine was prepared in a mass ratio of 1:1, tris(hydroxymethyl)aminomethane was added to adjust the pH to 8.5, and the mixture was stirred again to obtain a modified mixed solution; The pretreated continuous aramid fiber was immersed in the continuous aramid fiber, maintained at 37°C and 180 rpm for 24 hours, then taken out, impurities attached to the fiber surface were washed with deionized water, and then dried to obtain the polyethyleneimine-polydopamine modified continuous aramid fiber; (2) Dipping: adding methyl ethyl ketone peroxide (ACET) as an accelerator and cobalt cyclohexanecarboxylate (CO) as an initiator to unsaturated polyester resin as a glue solution, wherein the mass ratio of unsaturated polyester resin, methyl ethyl ketone peroxide and cobalt cyclohexanecarboxylate is 100:1:2; The polyethyleneimine-polydopamine modified continuous aramid fiber is placed in a glue solution for dipping at room temperature, and the excess resin is scraped off, and the dipping polyethyleneimine-polydopamine modified continuous aramid fiber is arranged according to the interlayer arrangement of collagen fibers of compact bone, and placed in a dry mold; (3) Curing: Apply a contact pressure of 10 MPa at the beginning of mold closing. After the unsaturated polyester resin turns into a gel state, place the mold in an oven and cure it at 60°C for 12 hours to obtain a high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material.

[0008] Furthermore, the aramid fiber is para-aramid fiber, Kevlar 29, 1500 D.

[0009] Furthermore, when the mixed solution of polydopamine and polyethyleneimine described in step (1) is prepared, the concentration of the polydopamine solution is 2 mg / ml, the concentration of polyethyleneimine is 2 mg / ml, and the mass concentration ratio of the polydopamine to the polyethyleneimine is 1:1.

[0010] The unsaturated polyester resin in step (2) is 191 type unsaturated polyester. When the resin is cured, a promoter is first added to the unsaturated polyester resin, and then an initiator is added and stirred evenly after mixing. The continuous aramid fiber is impregnated with the resin before the resin reaches a gel state.

[0011] The present invention also provides a high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material prepared by the method.

[0012] The present invention provides an easy-to-operate continuous aramid fiber modification method and a bionic structure of a continuous aramid fiber / unsaturated polyester resin composite material. The modification method grafts polydopamine and polyethyleneimine onto the continuous aramid fiber through the Michael addition reaction and Schiff base reaction of polydopamine and polyethyleneimine, and at the same time, the modified continuous aramid fiber bionics the layered arrangement structure of collagen fibers in compact bone, thereby preparing a high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material.

[0013] The aramid fiber is para-aramid fiber, Kevlar 29, 1500 D. In addition, the method of the present invention can also be applied to other existing types of aramid fibers. After being treated by the present invention, these aramid fibers will not be adversely affected, and these aramid fibers are also within the protection scope of the present invention.

[0014] The present invention adopts dopamine and polyethyleneimine to carry out surface chemical modification on continuous aramid fibers, and the modification preparation conditions are mild, the operation is simple, and it is easy to realize industrial large-scale production; the present invention adopts simple and mild operation to carry out surface modification on continuous aramid fibers to improve the interface bonding ability between continuous aramid fibers and unsaturated polyester resin, and prepares continuous aramid fiber / unsaturated polyester resin composite materials by biomimetic layer-by-layer arrangement structure of collagen fibers of compact bone, which has good tensile strength and fatigue resistance; the high-strength and fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite materials provided by the present invention are expected to be widely used as main load-bearing materials in multiple technical fields such as deep-sea mining, medical equipment, aerospace, etc. due to their excellent tensile strength and fatigue resistance.

[0015] The present invention simulates the layered arrangement structure of collagen fibers in human compact bone and arranges the modified aramid fibers in an oriented manner to prepare an aramid fiber / unsaturated polyester resin composite material with high strength and fatigue resistance. The interface bonding strength of the obtained material reaches 40.60 MPa and the tensile strength reaches 959.07 MPa, which is 82.47% higher than that of the unmodified continuous aramid fiber composite material and 34.19% higher than that of the unmodified continuous aramid fiber composite material. The fatigue life at 600 MPa reaches 760,000 times, which is 385% higher than that of the unmodified continuous aramid fiber composite material (160,000 times); the fatigue life at 500 MPa reaches 10.47 million times, which is 273% higher than that of the unmodified continuous aramid fiber composite material (2.81 million times); the fatigue life at 400 MPa reaches 87.1 million times, which is 247% higher than that of the unmodified continuous aramid fiber composite material (25.11 million times). Moreover, the process is simple, easy to mass produce, and low in cost, which is of great significance in the fields of scientific research and practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1The stress-strain curve (A), tensile strength (B), Young's modulus (C), and elongation at break (D) of unsaturated polyester resin under different curing processes; Figure 2 This is a scanning electron microscope image of the surface of polyethyleneimine-polydopamine modified continuous aramid fiber (PEI-PDA-AF) in Example 1 of the present invention; Figure 3 The stress-strain curve (A) and the interface bonding strength (B) of the continuous aramid fiber / unsaturated polyester resin transverse tow composite material of the present invention; Figure 4 A is a scanning electron microscope image of a cross section of a continuous aramid fiber / unsaturated polyester resin transverse tow composite material of the present invention, A is a scanning electron microscope image of a cross section of a polyethyleneimine-polydopamine modified aramid fiber / unsaturated polyester resin transverse tow composite material, B is a scanning electron microscope image of a cross section of a polydopamine-aramid fiber / unsaturated polyester resin transverse tow composite material, and C is a scanning electron microscope image of a cross section of an unmodified aramid fiber / unsaturated polyester resin transverse tow composite material; Figure 5 The stress-strain curve (A) and tensile strength (B) of the continuous aramid fiber / unsaturated polyester resin composite material of the present invention; Figure 6 A is a scanning electron microscope image of a tensile cross section of a continuous aramid fiber / unsaturated polyester resin composite material of the present invention, A is a scanning electron microscope image of a tensile cross section of a polyethyleneimine-polydopamine modified aramid fiber / unsaturated polyester resin composite material, B is a scanning electron microscope image of a tensile cross section of a polydopamine-aramid fiber / unsaturated polyester resin composite material, and C is a scanning electron microscope image of a tensile cross section of an unmodified aramid fiber / unsaturated polyester resin composite material; Figure 7 The fatigue life curves of the polyethyleneimine-polydopamine modified aramid fiber / unsaturated polyester resin composite material (PEI-PDA-AF / UP) and the unmodified aramid fiber / unsaturated polyester resin composite material (AF / UP) of the present invention; Figure 8 This is a scanning electron microscope image of the surface of the polydopamine-modified continuous aramid fiber in Comparative Example 1 of the present invention; Fig. 9 This is a scanning electron microscope image of the surface of the unmodified continuous aramid fiber in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0019] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0020] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.

[0021] Unsaturated polyester resin curing process optimization experiment example: By determining the optimal curing process of unsaturated polyester resin, the optimal curing process of polyethyleneimine-polydopamine-continuous aramid fiber / unsaturated polyester resin composite material is determined. It includes curing temperature and curing time, and its specific contents are as follows: Add methyl ethyl ketone peroxide as an accelerator and cobalt cyclohexanecarboxylate as an initiator to the unsaturated polyester resin, wherein the mass ratio of the unsaturated polyester resin, methyl ethyl ketone peroxide and cobalt cyclohexanecarboxylate is 100:1:2. Stir the mixture evenly and pour it into a dumbbell-shaped mold and let it stand for 30 minutes until it becomes a gel state.

[0022] The mold was placed at 25°C for 12 hours, 60°C for 2 hours, 60°C for 6 hours, 60°C for 12 hours, and 60°C for 24 hours, then taken out and the tensile strength was measured when it returned to room temperature.

[0023] like Figure 1Shown are the stress-strain curve, tensile strength, Young's modulus, and elongation at break of unsaturated polyester resin under different curing processes. As can be seen from the figure, when the temperature rises from 25°C to 60°C, the tensile strength of the unsaturated polyester resin increases significantly, and the elongation at break decreases significantly, which shows that temperature is the main influencing factor in the curing process, so 60°C is selected as the curing temperature. When cured at 60°C, the tensile strengths of the curing times of 12 hours and 24 hours are 53.53 MPa and 56.77 MPa, respectively, which are not much different. Considering the experimental cost, the present invention selects 12 hours as the curing time for the continuous aramid fiber / unsaturated polyester resin composite material. In summary of the above experimental examples, the best curing process selected by the present invention is a curing time of 12 hours at 60°C after the resin is in a gel state.

[0024] Example 1: Preparation and performance characterization of a polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material, the specific contents are as follows: The continuous aramid fiber was soaked in ethyl acetate for 24 hours for surface pretreatment to remove impurities on the fiber surface and then dried. A solution (pH = 8.5) with a dopamine ratio of 2 mg / ml and polyethyleneimine of 1:1 was prepared, and the continuous aramid fiber was placed in the solution and soaked at 37°C for 24 hours. After the reaction was completed, the continuous aramid fiber was taken out and washed with deionized water to clean the surface, and placed in a 60°C oven for 12 hours to obtain polyethyleneimine-polydopamine modified continuous aramid fiber. Figure 2 This is a scanning electron microscope image of polyethyleneimine-polydopamine modified continuous aramid fiber. The fiber surface is rough and a large area of ​​dense coating appears.

[0025] The polyethyleneimine-polydopamine modified continuous aramid fiber was dipped in resin, the excess resin was scraped off, and it was laid horizontally in the mold of the transverse tow composite material. The unsaturated polyester resin was slowly injected into the mold to fill the mold, and a layer of clean release paper was covered. The initial contact pressure was 10MPa; after the resin gelled, it was placed in an oven for curing at 60℃ for 12 hours. The interface bonding strength of polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin transverse tow composite material is shown in Figure 3 , the interface bonding strength reached 40.60 MPa. Figure 4 (A) is a scanning electron microscope image of the tensile cross-section of the polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin transverse tow composite material. There is a lot of resin residue on the surface of the continuous aramid fiber, and the resin matrix is ​​peeled off from the fiber surface, resulting in multi-layer peeling phenomenon.

[0026] The polyethyleneimine-polydopamine modified continuous aramid fiber was dipped in resin, and the excess resin was scraped off. The dipped fiber was stacked in a mold at 30° in the interlayer arrangement of collagen fibers of compact bone, and a contact pressure of about 10MPa was applied initially; after the resin gelled, it was placed in an oven for curing at 60°C for 12 hours. The tensile stress-strain and tensile strength of the polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material are shown in Figure 2. Figure 5 As shown, its tensile strength reaches 959.07 MPa. Figure 6 (A) is a scanning electron microscope image of the tensile cross-section of polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material. It can be clearly observed that the filament structure produced by the fiber being pulled out of the resin consumes more energy. The fatigue life curve of polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material is shown in Figure 2. Figure 7 As shown in the figure, the fatigue life gradually decreases with the increase of stress level. The fatigue life under 600 MPa reaches 760,000 times, the fatigue life under 500 MPa reaches 10.47 million times, and the fatigue life under 400 MPa reaches 87.10 million times.

[0027] Comparative Example 1: Preparation and performance characterization of a polydopamine-modified continuous aramid fiber / unsaturated polyester resin composite material. Compared with Example 1, the polydopamine-modified continuous aramid fiber was not grafted with polyethyleneimine. The specific contents are as follows: The continuous aramid fiber was soaked in ethyl acetate for 24 hours for surface pretreatment to remove impurities on the fiber surface and then dried. A 2 mg / ml dopamine and polyethyleneimine solution (pH = 8.5) was prepared, and the continuous aramid fiber was placed in the solution and soaked at 37°C for 24 hours. After the reaction was completed, the fiber was taken out and the surface was washed clean with deionized water, and placed in a 60°C oven for 12 hours to obtain polydopamine-modified continuous aramid fiber. Figure 8 This is a scanning electron microscope image of polydopamine-modified continuous aramid fiber. The fiber surface is rough, with layered deposits, and an adhesion coating is formed on the fiber surface.

[0028] The polydopamine modified continuous aramid fiber was dipped in resin, the excess resin was scraped off, and it was laid horizontally in the mold of the transverse tow composite material. The unsaturated polyester resin was slowly injected into the mold to fill the mold, and the resin was put into the oven for curing after the gel state was reached. The interface bonding strength of the polydopamine modified continuous aramid fiber / unsaturated polyester resin transverse tow composite material was 29.12 MPa ( Figure 3 The microscopic morphology of the tensile section of the polydopamine modified continuous aramid fiber / unsaturated polyester resin transverse tow composite material is shown in Figure 2. Figure 4 As shown in (B), there is resin residue on the surface of the continuous aramid fiber.

[0029] The polydopamine modified continuous aramid fiber was dipped in resin, and the excess resin was scraped off. The dipped fiber was stacked in layers in a 30° arrangement of the collagen fiber layers of the bionic compact bone in the mold, and the initial contact pressure was about 10 MPa; after the resin gel state, it was placed in an oven for curing at 60°C for 12 hours. The tensile stress-strain and tensile strength of the polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material are shown in Figure 2. Figure 5 As shown, its tensile strength reaches 836.85 MPa. Figure 6 (B) is a scanning electron microscope image of the tensile cross-section of the polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material.

[0030] Comparative Example 2: Preparation and performance characterization of a continuous aramid fiber / unsaturated polyester resin composite material. Compared with Example 1, the continuous aramid fiber was not surface modified with polyethyleneimine-polydopamine. The specific contents are as follows: The aramid fiber was soaked in ethyl acetate for 24 hours for surface pretreatment to remove impurities on the fiber surface and then dried. Fig. 9 This is a scanning electron microscope image of continuous aramid fiber. It can be seen that there are fine grooves and pits on the fiber surface. The continuous aramid fiber is dipped in resin, the excess resin is scraped off, and it is laid horizontally in the mold of the transverse tow composite material. The unsaturated polyester resin is slowly injected into the mold to fill the mold. The contact pressure is applied at the beginning, and the pressure is about 10 MPa; after waiting for the resin to gel, it is placed in an oven for curing at 60°C for 12 hours. The interfacial bonding strength of the continuous aramid fiber / unsaturated polyester resin transverse tow composite material is 22.25 MPa ( Figure 3 ), Figure 4 (C) is a scanning electron microscope image of the tensile cross-section of the polydopamine-modified continuous aramid fiber / unsaturated polyester resin transverse tow composite material. Only a trace amount of resin remains on the surface of the continuous aramid fiber.

[0031] The continuous aramid fiber was dipped in resin, and the excess resin was scraped off. The dipped fiber was stacked in layers in a 30° arrangement in the collagen fiber interlayer arrangement of compact bone in the mold, and the initial contact pressure was about 10 MPa; after waiting for the resin to gel, it was placed in an oven for curing at 60°C for 12 hours. The tensile stress-strain and tensile strength of the continuous aramid fiber / unsaturated polyester resin composite material are shown in Figure 2. Figure 5 As shown, its tensile strength reaches 714.71 MPa. Figure 6 (C) is a scanning electron microscope image of the tensile cross section of the continuous aramid fiber / unsaturated polyester resin composite material. The fatigue life curve of the unmodified continuous aramid fiber / unsaturated polyester resin composite material is shown in Figure 7As shown in the figure, the fatigue life gradually decreases with the increase of stress level. The fatigue life under 600 MPa is 160,000 times, the fatigue life under 500 MPa reaches 2.81 million times, and the fatigue life under 400 MPa reaches 25.11 million times.

[0032] By comparing and analyzing the above-mentioned Example 1 and Comparative Example 2, the performance-related parameters of the polyethyleneimine-polydopamine-continuous aramid fiber / unsaturated polyester resin (PEI-PDA-AF / UP) composite material and the unmodified continuous aramid fiber / unsaturated polyester resin (AF / UP) composite material are shown in Table 1. The interfacial bonding strength of the polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin composite material reached 40.60 MPa, which was 82.47% higher than that of the unmodified continuous aramid fiber composite material; the tensile strength reached 959.07 MPa, which was 34.19% higher than that of the unmodified continuous aramid fiber composite material. The fatigue life at 600 MPa reached 760,000 times, which was 385% higher than that of the unmodified continuous aramid fiber composite material (160,000 times); the fatigue life at 500 MPa reached 10.47 million times, which was 273% higher than that of the unmodified continuous aramid fiber composite material (2.81 million times); the fatigue life at 400 MPa reached 87.10 million times, which was 247% higher than that of the unmodified continuous aramid fiber composite material (25.11 million times).

[0033] Table 1 Comparison of properties of polyethyleneimine-polydopamine modified continuous aramid fiber / unsaturated polyester resin (PEI-PDA-AF / UP) composites and unmodified continuous aramid fiber / unsaturated polyester resin (AF / UP) composites Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material, characterized in that: Unsaturated polyester resin was used as the matrix and polyethyleneimine-polydopamine modified continuous aramid fibers were used as reinforcement. Polydopamine and polyethyleneimine were grafted onto the continuous aramid fibers by utilizing the Michael addition reaction and Schiff base reaction of polydopamine and polyethyleneimine. The modified continuous aramid fibers were made to mimic the collagen fiber arrangement structure of compact bone to prepare high-strength and fatigue-resistant continuous aramid fiber / unsaturated polyester resin composites.

2. The preparation method according to claim 1, characterized in that: The steps include: (1) Surface modification of continuous aramid fibers: The continuous aramid fibers were pretreated by soaking in ethyl acetate for 24 hours to remove impurities on the fiber surface and then dried; A mixed solution of polydopamine and polyethyleneimine was prepared in a mass ratio of 1:1, tris(hydroxymethyl)aminomethane was added to adjust the pH to 8.5, and the mixture was stirred again to obtain a modified mixed solution; The pretreated continuous aramid fiber was immersed in the continuous aramid fiber, maintained at 37°C and 180 rpm for 24 hours, then taken out, impurities attached to the fiber surface were washed with deionized water, and then dried to obtain the polyethyleneimine-polydopamine modified continuous aramid fiber; (2) Dipping: adding methyl ethyl ketone peroxide (ACET) as an accelerator and cobalt cyclohexanecarboxylate (CO) as an initiator to unsaturated polyester resin as a glue solution, wherein the mass ratio of unsaturated polyester resin, methyl ethyl ketone peroxide and cobalt cyclohexanecarboxylate is 100:1:2; The polyethyleneimine-polydopamine modified continuous aramid fiber is placed in a glue solution for dipping at room temperature, and the excess resin is scraped off, and the polyethyleneimine-polydopamine modified continuous aramid fiber is arranged according to the interlayer arrangement structure of the collagen fiber of the compact bone, and placed in a dry mold; (3) Curing: Apply a contact pressure of 10 MPa at the beginning of mold closing. After the unsaturated polyester resin turns into a gel state, place the mold in an oven and cure it at 60°C for 12 hours to obtain a high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material.

3. The preparation method according to claim 2, characterized in that: The aramid fiber is para-aramid fiber, Kevlar 29, 1500 D.

4. The preparation method according to claim 2, characterized in that: When the mixed solution of polydopamine and polyethyleneimine described in step (1) is prepared, the concentration of the polydopamine solution is 2 mg / ml, the concentration of polyethyleneimine is 2 mg / ml, and the mass concentration ratio of the polydopamine to the polyethyleneimine is 1:

1.

5. The preparation method according to claim 2, characterized in that: The unsaturated polyester resin in step (2) is 191 type unsaturated polyester. When the resin is cured, a promoter is first added to the unsaturated polyester resin, and then an initiator is added and stirred evenly after mixing. The continuous aramid fiber is impregnated with the resin before the resin reaches a gel state.

6. A high-strength, fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material prepared by the method according to any one of claims 1 to 5.

7. The high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material according to claim 6, characterized in that: The continuous aramid fiber in the high-strength fatigue-resistant continuous aramid fiber / unsaturated polyester resin composite material is oriented in a dense structure of bionic dense collagen fibers, with an interface bonding strength of 40.60 MPa and a tensile strength of 959.07 MPa. The fatigue life at 600 MPa reaches 760,000 times, the fatigue life at 500 MPa reaches 10.47 million times, and the fatigue life at 400 MPa reaches 87.1 million times.

Citation Information

Patent Citations

  • Aramid-fiber-reinforced flame-retardant unsaturated polyester composite material

    CN103160096A

  • Preparation method of biomimetic cartilage doped ordered magnetic nano-short fibers spliced double-layer hydrogel

    CN109836595A

  • Preparation method of dopamine modified glass fiber / unsaturated polyester composite material

    CN110093022A

  • Heald frame made of fiber-reinforced composite material

    JP2006138040A

  • Carbon fiber reinforced plastics using polydopamine and the manufacturing method thereof

    KR1020140121019A